Social media in public diplomacy : survey on the social media communication of the Finnish missions abroad - Nurmi, Maria (2012)
Today, social media is changing the way people communicate by giving the influence to the hands of the people. For organizations, it means that the issues of stakeholders are the focus of the communication, not the organizations. The question no longer is whether to use social media in public relations, but how to use it.